The Future of Indigenous Economic Development in Canada : Why it Matters - Rashwan , Mohammed (Economic Development Journal of Canada, 2025)
Indigenous Economic Development is a rapidly growing phenomenon in Canada. We are seeing steadily increasing labour force participation rates among both Indigenous men and women. From western, central, to eastern Canada, governments at the federal, provincial, and municipal levels are providing and creating rewards, procurement, and incentive programs geared towards Indigenous communities and businesses. This support includes assistance in the facilitation of higher education attainment to acquire rewarding and fulfilling careers such as the skilled trades or to aid Indigenous businesses in growth. However, there are some barriers to achieving the goal of parity that the National Indigenous Economic Development Board had for the current year of 2022. In some cases, obstacles are logistical and financial, in others they are related to education. The future of Indigenous Economic Development in Canada is not only one that is prosperous and fruitful for the communities involved but for the entire country as a whole.